Data from the All of Us research program reinforces existence of activity inequality - Hayoung Jeong; Ali R. Roghanizad; Hiral Master; Juseong Kim; Aymone Kouame; Paul A. Harris; Melissa Basford; Kayla Marginean; Jessilyn Dunn (npj Digital Medicine)
Abstract Large-scale and detailed analyses of activity in the United States (US) remain limited. In this work, we leveraged the comprehensive wearable, demographic, and survey data from the All of Us Research Program, the largest and most diverse population health study in the US to date, to apply and extend the previous global findings on activity inequality within the context of the US. We found that daily steps differed by sex at birth, age, body characteristics, geography, and built environment. Quantifying activity inequality using the modified Gini index, we found a strong correlation with obesity prevalence (R 2 = 0.804) and a moderate correlation with perceived walkability (R 2 = 0.426) and the activity gender gap (R 2 = 0.385). This study demonstrates the value of digital health technologies in exploring and understanding public health practices while highlighting the need to examine complexities, including biopsychosocial factors that may contribute to activity inequality.